2021
DOI: 10.1111/apt.16490
|View full text |Cite
|
Sign up to set email alerts
|

Nonselective beta‐blockers are associated with a lower risk of hepatocellular carcinoma among cirrhotic patients in the United States

Abstract: Karn Wijarnpreecha and Fang Li shared co-first authorship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 43 publications
2
21
1
Order By: Relevance
“…The results of the subgroup analysis revealed that the carvedilol monotherapy group did not have a significantly lower incidence of HCC than did the nonusers, although the adjusted HR for the carvedilol group was lower than that for the propranolol group. A study demonstrated a significantly lower risk of HCC in patients with cirrhosis by using carvedilol, propranolol, and nadolol (Wijarnpreecha et al, 2021). This finding differs from that of this study possibly because of differences in disease severity between the two studies.…”
Section: Discussioncontrasting
confidence: 98%
See 4 more Smart Citations
“…The results of the subgroup analysis revealed that the carvedilol monotherapy group did not have a significantly lower incidence of HCC than did the nonusers, although the adjusted HR for the carvedilol group was lower than that for the propranolol group. A study demonstrated a significantly lower risk of HCC in patients with cirrhosis by using carvedilol, propranolol, and nadolol (Wijarnpreecha et al, 2021). This finding differs from that of this study possibly because of differences in disease severity between the two studies.…”
Section: Discussioncontrasting
confidence: 98%
“…Studies have reported a more significant protective effect on HCC incidence in patients with HCV-or alcohol-related cirrhosis than in those with HBV-related cirrhosis (Kim et al, 2012;Nkontchou et al, 2012;Herrera et al, 2016;Yeh et al, 2019). The results of our study are consistent with those of a stratified analysis of patients with HBV-associated cirrhosis (Wijarnpreecha et al, 2021). Tolerant doses to NSBBs in different ethnic groups may have resulted in no remarkable effect on HCC prevention in this study.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations